Feeding Dentex dentex with dry diets: Growth response and diet utilisation - Cardenete G.; Skalli A.; Hidalgo M.C.; Abellán E.; Massuti S. (Feeding tomorrow's fish, 1997)
Common dentex is a Mediterranean sparid that has been put forward by several authors as being highly suitable for intensive aquaculture. Nevertheless, the basic nutrient requirements for this species have not been studied and the available information concerning the suitability of commercial diets used for rearing other sparid fish for dentex is scarce. In an initial experiment, we took fish of 100 g average initial weight and fed them on four commercial pellet diets (three sea bream feeds and one extruded diet for turbot), using fresh food as a control. One of the diets tested (58 per cent protein DM, 24.7 per cent fat DM and 24.4 KJ.g-1 of gross energy) produced a high survival index (90.5 per cent), as well as a good Instant Daily Growth (0.72) and Food Conversion Ratio (1.8), with results very close to those obtained with fish fed the fresh food control ration. A second trial was conducted using fish of 60 g average initial weight, fed at 2 per cent (Dm basis) with fresh food or with a practical diet (diet composition on dry matter basis: 57.4 per cent protein, 14.4 per cent fat and 21.8 KJ.g-1 of gross energy). Mortality was very low in all tanks, and the best growth performance and diet utilisation was observed in fish fed dry diet. In addition, dietary canthaxanthin added to the diet (50 ppm) was found to preserve the natural skin colour of the animals. These results confirm the possibilities of dentex intensive rearing using dry artificial diets.
Workshop of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1996/06/24-26, Mazarrón (Spain)